Protective Effect of Pogostone on 2,4,6-Trinitrobenzenesulfonic Acid-Induced Experimental Colitis via Inhibition of T Helper Cell - Jiyan Su; Jiyan Su; Cailan Li; Xiuting Yu; Guanghua Yang; Jianhua Deng; Ziren Su; Huifang Zeng; Jiannan Chen; Xiaojun Zhang; Xiaoping Lai (Frontiers Media S.A., 2017)
Inflammatory bowel disease (IBD) is a chronic immune-related disease mainly caused by the disequilibrium of T helper (Th) cell paradigm? Pogostone (PO) is one of the major chemical constituents of Pogostemon cablin (Blanco) Benth. The present study aims to investigate the potential benefit of PO against IBD in a 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced experimental colitis model. PO treatment by enema significantly brought down the disease activity index (DAI) of the TNBS-challenged rats, which was manifested by the ameliorated inflammatory features including ulceration, adhesion, and edema. Hematoxylin-eosin (HE) staining and immunohistochemistry analysis showed that PO effectively relived colon damage by restoring epithelium, and more importantly, by inhibiting the infiltration of pro-inflammatory Th1 and Th17 cells in the colon. Additionally, PO inhibited the activity of myeloperoxidase and secretion of inflammatory cytokines including IFN-γ, IL-12p70, IL-17A, and IL-10. Together with our previous findings, the present data indicated that the anti-IBD effect of PO probably related to its direct inhibition on Th cell proliferation and suppression of the cytokines secretion. These results highlighted the potential of PO as a promising candidate to relieve IBD.